Post-dispersion humidity condition alters the surface of the testa and the proportion of seeds with physical dormancy in Erythrina speciosa - Magalhães, Camila R.; Garcia, Queila S.; Oliveira, Denise M.T. (Seed science research, 2021)
Seeds of Papilionoideae (Leguminosae) species lose water after dispersal, increasing the proportion of water-impermeable seeds (physical dormancy, PY). However, changes in testa structure during this process remain unknown. The present study investigated how variation in relative humidity (RH) during the post-dispersion period affects the proportion of seeds of Erythrina speciosa with PY. Seeds from two populations were stored in drier (40% RH) and wetter (80% RH) environments and periodically subjected to physiological analysis (seed water content, imbibition and germination) and structural analysis of the testa (light and scanning electron microscopy). Drier storage resulted in seed dehydration, increasing the proportion of water-impermeable seeds and closure of cracks in the mucilaginous stratum. In contrast, wetter storage led to an increase in seed water content, a decrease in the proportion of seeds with PY, and the formation of cracks. As a result of variation in environmental humidity, we conclude that changes occur in the mucilaginous stratum of seeds, altering water loss and, consequently, the proportion of seeds with PY. Environments with low humidity cause a decrease in seed water content, the closing of cracks in the mucilaginous stratum, and, consequently, an increase in the proportion of water-impermeable seeds. On the other hand, a high RH environment increases the seed water content and the formation of superficial cracks, through which water enters during imbibition, causing a decrease in the proportion of seeds with PY.